PENGARUH PROBLEM-BASED LEARNING (PBL) BERSTRATEGI â€œMURDERâ€ TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Fatimah, Lutfiah; Maulana, M.; Isrok'atun, I. (Jurnal Pena Ilmiah, 2017)
The use of Problem-Based Learning (PBL) with â€œMURDERâ€ strategy in primary schools is still rare in Indonesia. Problem-Based Learning (PBL) strategy